2023
DOI: 10.1111/jon.13124
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in neurology: A comprehensive analysis and review

Abstract: Neurologists in both the inpatient and outpatient settings are increasingly using ultrasound to diagnose and manage common neurological diseases. Advantages include cost‐effectiveness, the lack of exposure to ionizing radiation, and the ability to perform at the bedside to provide real‐time data. There is a growing body of literature that supports using ultrasonography to improve diagnostic accuracy and aid in performing procedures. Despite the increasing utilization of this imaging modality in medicine, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…It is internationally recognized that the use of ultrasound by neurologists should be encouraged in the fields of neurovascular, neuro-intensive, neuromuscular, and point-of care ultrasound [2][3][4][5][6]. Guidelines for competency and quality assurance in the different fields of neurosonology have already been reported and can readily be implemented [3,4,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…It is internationally recognized that the use of ultrasound by neurologists should be encouraged in the fields of neurovascular, neuro-intensive, neuromuscular, and point-of care ultrasound [2][3][4][5][6]. Guidelines for competency and quality assurance in the different fields of neurosonology have already been reported and can readily be implemented [3,4,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging enables noninvasive, real-time visualization of soft tissues, including nerves, muscles, and blood vessels. [ 11 ] Some studies have investigated the accuracy of surface anatomy-guided injections in the cervical muscles, including the LS. [ 8 , 9 , 12 ] Ko et al compared the precision of ultrasound-guided and non-guided injection techniques (Perotto technique) in cadaveric cervical muscles, such as the levator scapulae, splenius capitis, and scalenus anterior and medius muscles, and found that ultrasound guidance was significantly more accurate (95.8% vs 54.2%, P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle ultrasound is a well-established tool for screening, diagnosis, and follow-up of acute and chronic clinical conditions in neuromuscular and metabolic disorders [ 4 ]. The assessment of muscle quantity and quality has proven valuable in a variety of pathologies such as severe critical illness, muscular dystrophies and myositis, peripheral neuropathies, cancer, and type 2 diabetes mellitus [ 5 , 6 , 7 , 8 , 9 ]. Echo intensity (EI) as determined by B-mode ultrasound is an accepted marker for muscle quality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%